WTO negotiations and agricultural trade liberalization: the effect of developed countries' policies on developing countries - Díaz-Bonilla, Eugenio; Frandsen, Søren Elkjær; Robinson, Sherman (CAB International, 2006)
The purpose of this book is to analyze the effects of developed countries' agricultural policies on developing countries. The main focus is on food security, poverty and other topics such as multifunctionality, biotechnology and regional agreements, as an input to policy reform within the World Trade Organization (WTO) trade negotiations.